Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Simplify the expression –3(x + 3)2 – 3 + 3x. What is the simplified expression in standard form?

–3x2 – 18x – 27
–3x2 – 15x – 30
–3x2 + 3x + 6
–3x2 + 3x – 30


Sagot :

Answer:

-3x² - 15x - 30

Step-by-step explanation:

-3(x + 3)² - 3 + 3x

= -3 {(x + 3)(x + 3)} - 3 + 3x

= -3 {x² + 3x + 3x + 9} - 3 + 3x

= -3 {x² + 6x + 9} - 3 + 3x

multiply -3 by {x² + 6x + 9}

= -3x² - 18x - 27 - 3 + 3x

collect like terms

= -3x² - 18x + 3x - 27 - 3

= -3x² - 15x - 30